Border patrol: The rise and role of fact-checkers and their challenge to journalists' normative boundaries. (August 2021) - Singer, Jane B
Although most research to date has focused on leading US fact-checkers, similar initiatives are gaining strength all over the world. This study draws on a globally disseminated questionnaire, plus interviews with fact-checkers on four continents, to examine their role and reach in relation to other journalistic enterprises, as well as the challenges they face. A conceptual framework of journalistic boundary-setting helps guide the exploration.